2017
DOI: 10.1016/j.ijcha.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage function assessment and thrombus identification

Abstract: BackgroundThe diagnosis of thrombus in the left atrium in patients with persistent atrial fibrillation (AF) and may be inconsistent because of variability in thrombus morphology. In some cases it is challenging and requires unusual approach. New Doppler-derived methods might be helpful to identify such thrombi. We evaluated quantitative differences in mechanical function of the left atrial appendage (LAA) basal segments using tissue Doppler imaging (TDI)and speckle tracking echocardiography (STE) in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 55 publications
1
22
0
2
Order By: Relevance
“…LA systolic function decreases after PVI despite significant decrease in LA volume, within the stiff LA syndrome which is a consequence of LA myocardium scar formation [19] , [20] , [21] . However, LAA volume enlarges after PVI and due to scar formation including > 30% of the LA endocardium, LAA contraction accounts for>50% of complete LA contraction [14] , [21] , [22] , [23] , [24] . Moreover, the higher the LAA peak flow velocity, the greater the likelihood of sinus rhythm maintainance after cardioversion and ablation procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…LA systolic function decreases after PVI despite significant decrease in LA volume, within the stiff LA syndrome which is a consequence of LA myocardium scar formation [19] , [20] , [21] . However, LAA volume enlarges after PVI and due to scar formation including > 30% of the LA endocardium, LAA contraction accounts for>50% of complete LA contraction [14] , [21] , [22] , [23] , [24] . Moreover, the higher the LAA peak flow velocity, the greater the likelihood of sinus rhythm maintainance after cardioversion and ablation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Also, these two 3D-TEE LAA's parameters proved as significant predictors of AFR after ablation both in univariate and multivariate Cox regression analyiss, which was corrected for most usual AFR risk factors (age, sex, body mass index, hypertension). Moreover, Kurzawski et al showed that the lower values of LAA's lateral wall strain rate is a significant predictor of thrombi formation within LAA, regardless of the AF type and underlying rhythm during TEE assessement [14] . Our study also showed that a lower LAA ostium surface area is predictive for AFR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ablation lesion sets used over the past 15 years in ablating AF and AT can block many of the interatrial pathways (Figure ), endangering interatrial conduction. Partial block potentiates re‐entry; total block can isolate the LA body and LAA, facilitating thrombus formation …”
Section: Discussionmentioning
confidence: 99%